A discrete element modelling of gravity flow in sublevel caving considering the shape and size distribution of particles. Issue 4 (21st April 2023) - Firouzabadi, Mahdeyeh; Esmaeili, Kamran; Rashkolia, Gholamreza Saeedi; Asadi, Mohsen
ABSTRACT: One of the most significant challenges for cave mining methods is dilution, a process which is generally controlled by the gravity flow of caved materials. In this study, the discrete element method (DEM) was used to investigate the effects of changing the porosity of blasted ring material and caved waste rocks and of changing the ring inclination on material flow in a sublevel cave (SLC) mine. Yade software was used to simulate two-dimensional gravity flow in a longitudinal section of the sublevel while taking into consideration the shape and size distribution of the flowing rock particles. Four simulations were generated with different porosities, and the material flow in the models was compared to each other. The results demonstrate that when ring porosity is increased, dilution decreases, and the height of the extraction zone grows longitudinally. Also, a lower porosity of the blasted ore material in the ring can cause early dilution entry and expansion of the extraction zone towards the caved waste.. Finally, the effect of ring inclination on the material flow and dilution was investigated. The results of these simulations show an increased dilution as the ring inclination increases and a change in the shape of the extraction zone.